1995
DOI: 10.2166/wst.1995.0536
|View full text |Cite
|
Sign up to set email alerts
|

Urban wastewater treatment by electrocoagulation and flotation

Abstract: In waste water treatment, the use of a physico-chemical process by flotation would present some advantages compared to a separation by settling. However like each physico-chemical process, a separation by flotation needs a chemical destabilization. We have studied the use of an electrochemical destabilization coupled to a process of flotation (DAF). This paper presents the results obtained on an urban waste water treated by electrocoagulation and dissolved air flotation (DAF). To show the interest of coupling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
127
0
7

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(135 citation statements)
references
References 0 publications
1
127
0
7
Order By: Relevance
“…Some investigators have reported that in electrocoagulation, current density can influence the treatment efficiency (Pouet and Grasmick, 1995), while others have reported that current density has no significant effect on pollutant removal (Chen et al, 2000). Therefore, it remains unclear that whether the current density affects the treatment efficiency or not.…”
Section: Effect Of Current Densitymentioning
confidence: 99%
See 1 more Smart Citation
“…Some investigators have reported that in electrocoagulation, current density can influence the treatment efficiency (Pouet and Grasmick, 1995), while others have reported that current density has no significant effect on pollutant removal (Chen et al, 2000). Therefore, it remains unclear that whether the current density affects the treatment efficiency or not.…”
Section: Effect Of Current Densitymentioning
confidence: 99%
“…It has been applied for treatment of potable water (Vik et al, 1984;Holt et al, 2002), urban wastewater (Pouet and Grasmick, 1995), heavy metal laden wastewater (Mills, 2000), restaurant wastewater (Chen et al, 2000), and colored water (Jiang et al, 2002). Further, electrocoagulation offers possibility of anodic oxidation and in situ generation of adsorbents (such as hydrous ferric oxides, hydroxides of aluminum).…”
Section: Introductionmentioning
confidence: 99%
“…However, no further work in which electrocoagulation has been similarly applied has appeared in the literature since then. Instead, electrocoagulation (EC), an electrochemical technique by which a variety of unwanted dissolved particles and suspended matter, both organic and inorganic, can be effectively removed from an aqueous solution by electrolysis, has been mainly used to treat various aqueous organic and inorganic wastes [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], or sometimes as a method in clarifying potable water [20][21]. As an extension of the work by Miwa who used only aqueous plant extracts, we report here the dechlorophyllation of alcoholic plant extracts by electrocoagulation.…”
Section: Introductionmentioning
confidence: 99%
“…Some investigators have reported that current density can influence the treatment efficiency (Pouet and Grasmick 1995), but their conclusion was based on experimental conditions where the charge loading also varied. Other investigators have shown that the current density had no effect on the removal efficiency of electrocoagulation (Chen et al 2000).…”
Section: Charge Densitymentioning
confidence: 99%